Strengthening Student Engagement: How Student Hone Their Soft Skill Along Online Learning During Covid-19 Pandemic? - Valeny Suryaningsih (Universitas Pendidikan Nasional, 2021)
The objective of this research is to know how student hone their soft skill along online learning during Covid-19 pandemic. It is a descriptive research, applied through interview and questionnaire survey among 15 students taken Leadership Class, Academic Year of 2020-2021. This study has discovered by providing group discussion session, lecturer has generated enthusiasm for learning and student’s interaction during online learning. To enhance students’ soft skill along online learning, it is found by optimizing the usage of media and method of learning; up to date SLP, integrated the LMS with Whatsapp function through Collaborative Learning. Students are schooled by submitting mind mapping sub-subject task, class discussion, FGD team discussion, PPT submission and oral presentation in specific time limit every meeting. It is provided from up to date case studies in every meeting that help students in providing the practitioner's view, hone critical thinking, presentation and public speaking skills.